Design of current controlled instrumental amplifier by using complementary metallic oxide semiconductor technology - Ghanim Thiab Hasan; Kamil Jadu Ali; Ali Hlal Mutlaq (Institute of Advanced Engineering and Science, 2023)
In this paper, a complementary metal oxide semiconductor (CMOS) instrumental amplifier was designed and implemented in order to provide the possibility of controlling the current and voltage gain. The proposed instrumentation amplifier consists of three conveyors with active resistor. The parasitic resistance value (Rx) was reduced with a large bandwidth level in addition to achieving a high common mode rejection ratio (CMRR). Simulation was performed by using 0.35μm CMOS technology by using the advanced design system (ADS) software. The results obtained prove that the proposed circuit has a good efficiency with higher degree of CMRR in comparison with other amplifiers designed and implemented in other similar works.